Cushcush—Dioscorea trifida L. - James M. Stephens (EDIS)
This document provides an overview of cushcush (Dioscorea trifida), a lesser-known tropical yam native to the Caribbean. It describes the plant’s characteristics, cultivation methods, and culinary uses. Cushcush is valued for its flavor and cooking qualities but is not widely grown in the Americas due to the prevalence of other staple crops. The plant is a perennial vine producing edible tubers and requires warm climates and trellising for optimal growth. Although yields are lower than other yams, cushcush tubers are nutritious and versatile in cooking. Original publication date May 1994.